The effect of repeated preheating on diametral tensile strength of composite resin with different fillers - Ellen Winarta; Tien Suwartini; Anastasia Elsa Prahasti; Rosalina Tjandrawinata (Wolters Kluwer Medknow Publications, 2020)
Background: The development of adhesive systems has made the removal of carious lesion a minimally invasive procedure. Composite resin is the material of choice today, but the filler composition of the resin varies. Packable composite resin has good mechanical properties, but its high viscosity makes it hard to manipulate. Several methods, such as preheating, are used to decrease this viscosity. A syringe of composite resin might be preheated several times, but the effect of repeated preheating is unknown. Objectives: The purpose of this research was to analyze the effect of repeated preheating on the mechanical properties of a composite resin with different fillers. Method: Microhybrid, nanohybrid, and nanofill composite resins were preheated (ten times, twenty times, and control), molded into cylinder molds 6 mm in diameter and 3 mm in height, flattened with a celluloid strip, and polymerized with an light-emitting diode light-curing unit for 40 s. A total of 180 specimens were tested. The specimens were divided into two groups: Group 1 was immediately tested using a universal testing machine. Group 2 was soaked in 37°C artificial saliva for 24 h before testing. Each specimen was tested using the universal testing machine with the pressure side with a 1 mm/s crosshead speed. Result: Nanohybrid composite resin had the most stable diametral tensile strength after repeated preheating, whereas nanofill composite had the weakest strength. The increase and decrease in the diametral tensile strength in each group were not statistically significant. Conclusion: Repeated preheating does not significantly affect the diametral tensile strength of composite resin.